Sejarah Asal-Usul Penamaan dan Perkembangan Kawasan â€œOkuraâ€ di Pekanbaru pada Abad ke-20 - Amanan, Amanan (Mahesa Research Center (PT. Mahesa Global Publishing), 2023)
This research explores the History, Origin, and Development of the Okura Area, which originated from Okura Estate (plantation) in Pekanbaru in the 20th Century. The study employs a historical method, relying on toponymic analysis. The method includes heuristic, criticism, interpretation, and historiography steps. the techniques for collection the data are archival study, literature review, and interview. Okura Estate is one of the relatively large rubber plantations established by Baron K. Okura during the Dutch Colonial period. The existence of Okura Estate in Pekanbaru during the Dutch colonial period (in the 20th century) reflects life on plantations during that time, the role of the Japanese in the region, the involvement of external labor and the local community, and how these elements intertwined in the past, contributing to the cultural heritage in the Okura area that persists to this day. The research reveals the complexity behind historical, toponymic, environmental, and cultural aspects to uncover the evolution of Okura Estate over time.